1984
DOI: 10.1080/10408398409527399
|View full text |Cite
|
Sign up to set email alerts
|

Dry beans ofPhaseolus:A review. Part 3

Abstract: Beans of Phaseolus are important food crops both economically and nutritionally, and are cultivated and consumed world wide. With ever rising costs of meats, fresh fruits, and vegetables, dry beans are expected to contribute more to the human nutrition in coming years. Traditionally, they have been referred to as "poor man's meat" and have contributed significantly to the diets of many people of several countries in Asia, Africa, the Middle East, and South America. In recent years, a renewed interest in bean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 299 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Legumes are a very important source of dietary proteins for much of the world's population (Deshpande et al. 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Legumes are a very important source of dietary proteins for much of the world's population (Deshpande et al. 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that these anti‐nutrients can be eliminated or reduced significantly by processing techniques such as thermal heating (e.g. infrared heating, extrusion, irradiation, steam treatment and pelleting), milling, soaking, germination, fermentation, cooking and protein extraction (Deshpande et al ., 1984; Salunkhe & Kadam, 1989; van der Poel, 1990; Liener, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A major factor in the under‐use of legume products is the prolonged cooking requirements of beans before consumption. The production of quick‐cooking legumes, a process whereby dehydrated cooked beans could be reconstituted within 5–10 min, is an attempt to reduce the preparation time of legume products and has been successfully applied to a wide range of bean varieties ( Deshpande et al ., 1985 ). In the case of producing quick‐cooking red kidney beans, the process suffered from major drawbacks, mainly due to severe levels of bursting during industrial drying.…”
mentioning
confidence: 99%